ANALISIS KESULITAS BELAJAR SISWA DALAM PERSPEKTIF FILSAFAT PENDIDIKAN - Sartika Fitri Eka Lubis (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
Abstract: The success of the teaching and learning process is the achievement of student competition which includes knowledge, skills, and attitudes in each subject. The purpose of this study is to describe students' learning difficulties in the perspective of educational philosophy. This study uses a literature study method that relies on bibliographic sources from books and articles in scientific journals related to the subject matter. The results of this study indicate that: 1) The factors that cause learning difficulties consist of two kinds, including: a) Internal Factors Participants students, namely things or conditions that arise in the students themselves. Such as the low intellectual capacity / intelligence of students, unstable emotions and attitudes, and disruption of the senses of seeing and hearing. b) External factors of students, namely things or circumstances that come from outside the students themselves. Usually comes from the family environment, village/community environment and school environment. 2) The characteristics of the philosophy of education in learning include: a) theory of education, b) theory of learning, c) theory of students, d) theory of educators. Keywords: Learning Difficulties, Students, Educational Philosophy